DEVELOPMENT OF THE CORTICAL AND MEDULLARY CELLS OF ADRENAL GLAND IN THE LONG-TAILED MACAQUE (Macaca fascicularis) DURING PRE- AND POSTNATAL PERIOD - Danang Dwi Cahyadi; Nurhidayat Nurhidayat; Supratikno Supratikno; Savitri Novelina; Chairun Nisa'; Heru Setijanto (Universitas Syiah Kuala, 2019)
The study aimed to analyze the dynamics of the development of cortical and medullary cells of adrenal gland in the long-tailed macaque (Macaca fascicularis) during pre- and postnatal period. The samples of adrenal glands were taken from 5 fetuses aged 70, 85, 100, 120, and 150 days of gestation, a newborn aged 10, and an infant aged 105 days old. The samples of the adrenal glands were stained with hematoxylin-eosin and Masson trichrome (Goldner’s modification). The results showed that the fetal adrenal cortex consisted of a definitive and fetal zones, but in the late gestation (fetus aged 150 days of gestation), the transitional zone appeared between both zones. At the postnatal period, the definitive zone changed to glomerulosa zone, while the outer cells of the transitional zone changed to fasciculata zone which radially arranged. The results indicated that the fetal zone was present until birth and it will disappear gradually after birth. The medullary cells were found at the fetal stages as an irregular structure of small islands of chromaffin cells in the fetal zone. This structure migrated slowly to the center of the adrenal glands. The characteristics of mature chromaffin cells were found in the adrenal glands at postnatal period. In conclusion, the cortex adrenal of the newborn of long-tailed macaque consisted of zona glomerulosa, zona fasciculata, zona transitional, and the remaining fetal zone that has dissapeared gradually after birth.